Impatiens neo-uncinata (Balsaminaceae), a new species from southern Western Ghats of Kerala, India - Sindhu, Arya; Anil Kumar, Venugopalan Nair Saradhamma (Phytotaxa, 2024)
A new species, Impatiens neo-uncinata, belonging to section Scorpioidae is described and illustrated from Thiruvananthapuram district of Kerala in the southern Western Ghats. It is morphologically similar to Impatiens unicinata, but can easily be distinguished in having milky white distal lobe of keel petal, deltoid shape of standard petals and 1–2 seeded capsules. Furthermore, the SEM analysis of pollen and seed also delineate the taxa. Impatiens neo-uncinatais assessed here as Endangered based on the categories and criteria of the IUCN Red List.